Pengaruh Media Audio Visual Terhadap Hasil Belajar IPA Eksperimen Kelas VII MTs Qotrun Nada Depok - Miftah Abdul Latif (CV. Alim's Publishing, 2024)
The aim of the research is to determine the effect of implementing Audio Visual Learning Media on science learning outcomes by conducting experiments on class VIII students at MTs Qotrun Nada Depok. The research model used is an experimental method with analysis of the mean difference between two samples. The sample used was 40 students from classes VII.1 and VII.2 as the experimental class and 40 students from classes VII.3 and VII.4 as the control class. Research data to test the hypothesis comes from test scores on Measurement Materials and quantities. The instruments used are validity and reliability. The results of the research are the results of learning science using Audio Visual Learning Media (experimental class), with an average score of 72.30 with a median of 70.59; mode 68.42; variance 177.07; and standard deviation 13.31. It can be concluded that students' science learning outcomes provide good results. The science learning outcomes of students who did not use Audio Visual Learning Media (control class) obtained an average score of 50.85 with a median of 43.75; mode 47.17; variant 190.85; and standard deviation 13.81. This shows that students' science learning outcomes provide quite good results. So it can be concluded that there is an influence of Audio Visual Learning Media on science learning outcomes. From the research results, it was found that tcount = 7.13 was higher than ttable = 1.996 at a significance level of 5%, so H0 was rejected and H1 was accepted. This means that there is a significant difference between students' science learning outcomes taught with Audio Visual Learning Media. Keywords: ,